Land Use and Land Cover Change Analysis in Choke Mountain, Ethiopia (2013-2023) - Mekonnen , Assaye (Asian Journal of Environmental Research, 2025)
In this study, spatial and temporal trends of Land Use and Land Cover Change (LULCC) in Choke Mountain, Ethiopia, between 2013 and 2023 were explored employing a mixed-methods approach. Satellite imagery (Landsat 8 OLI/TIRS) was analyzed through supervised classification and post-classification change detection techniques, supported by field observations, key informant interviews, and focus group discussions. The results reveal extreme changes: agricultural land raised by 4.5% (1,207.95 ha), predominantly at the expense of grasslands (−11.9%) and shrublands (−34.8%). Forest cover unexpectedly raised by 28.6% (1,156.26 ha) due to Eucalyptus plantations, while natural forest decline persists. Settlement areas raised by 133%, which reflects heavy urbanization. Slope analysis revealed that 67.4% of the area is composed of gentle slopes (<30%), and 32.6% is composed of steep slopes that are susceptible to erosion. The main drivers of these changes are population growth, agricultural expansion, fuelwood requirements, and unsustainable land-use policies. These changes have deep implications for ecosystem services, soil conservation, and climate resilience in this critical Upper Blue Nile Basin region. The study recommends that integrated land-use planning, forest conservation programs, and sustainable agriculture practices are required to balance ecological integrity with livelihood needs. These findings constitute the scientific basis on which policymakers can base policies to facilitate sustainable land management in the highland ecosystems of Ethiopia.